2019
DOI: 10.5935/978-85-7042-109-8
|View full text |Cite
|
Sign up to set email alerts
|

Educação no Século XXI - Volume 18 - Especial - Inclusiva

Abstract: Modo de acesso: World Wide Web Inclui bibliografia 1. Educação 2. Infantil 3. Média 4. Tecnológica I. Título CDD-370 O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos seus respectivos autores www.poisson.com.br

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous reports on phytochemical studies of M. repandus stem extracts revealed that the plant contains an isocoumarin bergenin as one of its active constituents (Rivière et al 2010;Sriset et al 2021). Bergenin was examined in various anti-inflammatory models and was proven to be an efficient anti-inflammatory compound (Oliveira et al 2019). The compound has been thoroughly studied in terms of pharmacology and has emerged as a promising candidate for therapeutic uses (Mehta et al 2022).…”
Section: Determination Of Lupeol Content In Different Plant Extractsmentioning
confidence: 99%
“…Previous reports on phytochemical studies of M. repandus stem extracts revealed that the plant contains an isocoumarin bergenin as one of its active constituents (Rivière et al 2010;Sriset et al 2021). Bergenin was examined in various anti-inflammatory models and was proven to be an efficient anti-inflammatory compound (Oliveira et al 2019). The compound has been thoroughly studied in terms of pharmacology and has emerged as a promising candidate for therapeutic uses (Mehta et al 2022).…”
Section: Determination Of Lupeol Content In Different Plant Extractsmentioning
confidence: 99%